PENINGKATAN HASIL BELAJAR IPA MELALUI MODEL PEMBELAJARAN SNOWBALL THROWING DENGAN TERAPAN GERHANA (GERAK HARMONI BERTANYA) PADA SISWA KELAS VI SDN 57KOTA TERNATE - Nenny Febriany Abdul Karim (Direktorat Guru Pendidikan Dasar, Kemendikbudristek R.I., 2019)
The research objective is to know the learning implementation through Cooperative Learning Model with Snowball Throwing assisted with GERHANA (acronym of Gerak Harmoni Bertanya) on the children’s learning outcomes. The design was that of a Classroom Action Research, expecting an active, effective, efficient, and enthusiastic learning atmosphere. Actions were taken in two cycles, organized sequentially in planning, action, observation, and refection. Data were collected through observation and questionnaire. This research was collaboratively conducted with colleagues in SD Negeri 57 Kota Ternate. There were 30 children recruited as the subjects. Data analysis results show that the children’s learning outcomes improved from 53% in cycle I to 88% in cycle II. Whereas, the children’s learning activities were also improved from 69% in cycle I to 73% in cycle II. It can be concluded that the implementation of the Cooperative Learning Model assisted with the acronym GERHANA could enhance the children’s learning activities and outcomes.